Effects of Baduanjin Exercise on Physical Function and Health-Related Quality of Life in Peritoneal Dialysis Patients: A Randomized Trial - Fan Zhang (Frontiers Media S.A., 2021)
Background and Aims: Exercise is an efficient non-pharmacological intervention for chronic kidney disease. The study aims to evaluate the effects of Baduanjin exercise on physical function and health-related quality of life (HRQOL) in peritoneal dialysis (PD) patients.Methods: Seventy PD patients were randomly assigned to either the Baduanjin exercise group or the control group. Fifty-seven patients completed the study (exercise group, 25; control group, 32). The exercise group received the Baduanjin exercise program for 12 weeks. The control group received usual care. Three well-established performance-based tests determined physical function: five times sit-to-stand test (FTSST), timed up and go test (TUGT), and handgrip strength (HGS). HRQOL was assessed by the Kidney Disease Quality of Life-Short Form.Results: At baseline, no differences in physical function and HRQOL were observed between the Baduanjin exercise and the control group. At follow-up, the Baduanjin exercise group showed a marginally significant improvement in FTSST (P = 0.008) and TUGT (P = 0.040) over the 12 weeks compared to the control group. HRQOL in the Baduanjin exercise group was significantly higher than that of the control group.Conclusions: A 12-week Baduanjin exercise program may improve physical function and HRQOL in PD patients. Longer follow-up is needed to determine if these findings will translate into clinical application.